Calculation of physical properties of fats on their triacylgyclerole composition - Mazaeva, Viktoria; Demidov, Igor; Golodnyak, Vladimir; Onopriyenko, Tetyana (Technology audit and production reserves, 2017)
Studies on the development of fat bases with specified physical, chemical and organoleptic properties are given. To obtain fatty products with such properties, it is necessary to take into account the ratio of fats and oils in fat bases, as they affect the structure, stability, organoleptic characteristics and presentation of finished products. To determine the relationship between the physicochemical parameters and the concentration of the components in the mixture, Scheffe third-order simplex-lattice plan is used for the three-component mixture. Using a linear model, regression equations are obtained between the melting point, the pour point and the concentration of the components in the mixture. When the functional relationship between the triacylglycerol (TAG) composition and the physicochemical parameters is revealed, it is necessary to obtain the TAG composition of pure fats and mixtures. With the help of mathematical solutions, linear equations for TAG composition and physical and chemical parameters are obtained. With the help of the obtained mathematical model, the ratio of components in the new mixture is calculated for: palm olein (PO) x1=0.469, palm stearin (PS*) x2=0.255, hydrogenated fat M3 (HF) x3=0.276. The melting temperature which is equal to 40.3 ºС and pouring – 28.7 ºС are determined. This makes it possible to calculate fat bases of margarines with given properties.